Good stress or bad stress? An empirical study on the impact of time pressure on doctoral students’ innovative behavior - Zhang, Xin; Zhao, Zhixing; Sun, Jie; Ren, Jiajia (Frontiers in Psychology, 2024)
In recent years, with rapid societal advancement and profound transformations in knowledge production, doctoral students are increasingly facing significant time pressures. These pressures not only stem from an escalation in research tasks but also from urgent demands for innovative outputs. Grounded in Affective Events Theory, this study explores the dual impact of time pressure on the innovative behaviors of doctoral students in China. It specifically examines how challenge and hindrance time pressures affect doctoral students' innovative behavior through the mediating role of research self-efficacy and the moderating role of supervisor support. This research employed SPSS 26.0 and Mplus 8.3 for statistical analysis, analyzing multi-time point data collected from 452 Chinese doctoral students between May and August 2023. The results reveal that challenge time pressure significantly positively impacts doctoral students' innovative behavior, while hindrance time pressure has a significant negative impact. Furthermore, research self-efficacy partially mediates the relationship between both challenge and hindrance time pressures and innovative behavior. In this process, the moderating role of supervisor support is significant, enhancing the positive effects of challenge time pressure and mitigating the negative impacts of hindrance time pressure, highlighting the importance of supervisor support in optimizing the impact of time pressure and promoting doctoral students' innovative behavior. These findings not only enrich the theoretical framework in the field of time pressure research but also provide practical guidance for universities and supervisors on how to support doctoral students in effectively managing time pressure and fostering their innovation.